Dairy management practices - Armbruster, Jim.; Brady, Zach.; Davis, G. W.; Maddox, Bill.; Creative Educational Video, Inc. (Lubbock, TX : Creative Educational Video, Inc., 2008)
The presentation focuses on nine management practices essential to efficient dairy operations: artificial insemination, calving, calf management, heifer management, milking, dairy cow management, record keeping, hoof trimming, loading and transportation.
Fakulti Perubatan Veterinar.
Production coordinator, Zach Brady ; executive producer, G. W. Davis.
Hosted by Jim Armbruster ; narrated by Bill Maddox.
Keywords: Dairy cattle; Dairy farms -- Management; Dairying; Dairying -- Study and teaching; Milk yield